Analisis Dampak Pelatihan Emosional Spiritual Terhadap Kesadaran Diri pada Mahasiswa Program Studi Psikologi - Debi Angelina Br Barus; Maria Kami; Maria Margaretha Yustina; Agustina Vikariani Noeng; Inoccensia Olga Gapun; Theresia Yulyani; Donata Trifiyanti Walbaum; Fransiska Romana Uto Renggi (Action Research Journal, 2024)
Self-awareness is an individual's ability to identify and understand oneself completely, both in terms of nature, character, emotions, feelings, thoughts, and ways of adapting to the environment. Factors that influence self-awareness are factors that originate from the individual in the form of being able to manage spiritual emotions. The aim of this training is to find out to what extent spiritual emotional training can influence the self-awareness of 5th semester psychology students. The population in this study were psychology students using a simple random sampling technique. This research uses a quantitative experimental research method with a one-group experimental design, namely, a pre-test and a post-test. In this research, the spiritual-emotional scale is one of the measuring tools used. The results found that spiritual emotional training can increase self-awareness in 5th semester psychology students with a significant level (p) of 0.00 < 0.05.